2021
DOI: 10.1186/s12885-021-08670-2
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid switch from prednisone to dexamethasone in metastatic castration-resistant prostate cancer patients with biochemical progression on abiraterone acetate plus prednisone

Abstract: Background To assess the efficacies and potential predictors of a corticosteroid switch in metastatic castration-resistant prostate cancer (mCRPC) patients with biochemical progression on abiraterone acetate plus prednisone (A + P). Methods Patients with mCRPC treated between April 2016 and August 2020, who experienced biochemical progression on A + P and then switched to A plus dexamethasone (D), were retrospectively identified. The primary endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Nevertheless, recent clinical trials have demonstrated the benefit of using prednisone, instead of dexamethasone, in conjunction with docetaxel for the treatment of advanced prostate cancer [ 45 ]. Furthermore, Tanaka et al showed that docetaxel combined with 0.5 mg of dexamethasone orally twice a day results in a PSA response and good survival efficacy in castration-resistant prostate cancer [ 46 , 47 ], whereas other trials in patients with metastatic castration-resistant prostate cancer displayed benefits regarding switching corticosteroid from prednisone to dexamethasone after progression in abiraterone acetate [ 48 , 49 ]. This implies that particular patients with advanced prostate cancer might benefit from the use of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent clinical trials have demonstrated the benefit of using prednisone, instead of dexamethasone, in conjunction with docetaxel for the treatment of advanced prostate cancer [ 45 ]. Furthermore, Tanaka et al showed that docetaxel combined with 0.5 mg of dexamethasone orally twice a day results in a PSA response and good survival efficacy in castration-resistant prostate cancer [ 46 , 47 ], whereas other trials in patients with metastatic castration-resistant prostate cancer displayed benefits regarding switching corticosteroid from prednisone to dexamethasone after progression in abiraterone acetate [ 48 , 49 ]. This implies that particular patients with advanced prostate cancer might benefit from the use of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…The unique feature of systemic post-treatment after the study treatments in the ABI arm involved more frequent use of dexamethasone and ethinylestradiol. These drugs were reported to improve some outcomes in prostate cancer patients [26][27][28][29]. Dexamethasone was used for 0 and 3 patients in the ENZ and ABI arms, respectively, and ethinylestradiol was used for 2 and 5 patients in the ENZ and ABI arms, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…AA+prednisolone was administered according to the treatment protocol including 1,000 mg AA and 10 mg Frontiers in Pharmacology frontiersin.org prednisolone daily. The prednisolone can be changed to 0.5 mg dexamethasone when serum level of PSA increased and no other progression was present (Yang et al, 2021). A few patients to whom dexamethasone was administered before the AA treatment (Venkitaraman et al, 2008) started with the AA+dexamethasone combination (Attard et al, 2019).…”
Section: Treatmentmentioning
confidence: 99%
“…The overall survival was also investigated. During AA treatment, patients also receive a corticosteroid, typically prednisone/prednisolone or dexamethasone ( Yang et al, 2021 ). Therefore, two separate groups treated with AA were studied: those who received only prednisolone, and those who received dexamethasone.…”
Section: Introductionmentioning
confidence: 99%